Dos miradas sobre la mujer etrusca - Elvira Barba, Miguel Ángel (Anales de Historia del Arte, 2007)
This paper studies two concrete aspects of the role of women in Etruria in the VIth century BC: on the one part, her situation in society and family, and on the other, the possibilities that women had, within the previous context, of choosing their outward appearance and clothing. These questions will be analyzed using classical texts, inscriptions, and above all, Etruscan art of the Archaic Period.